Theories about pure social coordination with experimental evidence from Slovenia - Ule, Aljaž (Teorija in praksa, 2025)
The article presents a discussion of the results of laboratory experiments on social coordination that allowed various forms of reasoning to be used. The experiments were conducted in the TIG laboratory at the University of Primorska. We investigate the type of reasoning the participants used while making decisions in the laboratory. In particular, two contemporary theories of coordination are tested, the first describing a team-oriented and the second an individual-oriented type of thinking. T he participants’ coordination behaviour shows that young people hold the potential to develop both some form of cooperative reasoning and a more individualistic, boundedly rational focus on their own success, such as referred to in cognitive hierarchy theory. Instead of team reasoning, we f ind evidence in support for a simpler, albeit less profitable odd-one-out heuristic.
Keywords: bounded rationality; coordination problems; eksperimentalno odločanje; experimental decision-making; individualno usmerjeno mišljenje; individual-oriented reasoning; omejena racionalnost; problemi usklajevanja; team reasoning; timsko mišljenje; usklajevanja